2021
DOI: 10.1109/jsyst.2020.3014205
|View full text |Cite
|
Sign up to set email alerts
|

NOMA-Aided Multi-UAV Communications in Full-Duplex Heterogeneous Networks

Abstract: To address spectrum scarcity in unmanned aerial vehicle (UAV) communications, non-orthogonal multiple access (NOMA) aided multi-UAV communications in full-duplex (FD) heterogeneous networks (HetNets) is investigated in this paper. Specifically, an ergodic capacity analysis of NOMA-aided multi-UAV communications in FD-HetNets is conducted through a moment generating function (MGF) approach within a stochastic geometry framework. By employing the MGF approach to evaluate ergodic capacity, exact expressions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The road to realize 6G networking includes radical departures from conventional wireless architectures, where highly dynamic nodes are deployed to different network areas, ensuring increased resiliency against outages [15], [16]. Moreover, UAVs act as an intermediate layer to terrestrial and satellite segments, providing connectivity in remote and rural environments, fast recovery from disasters, and ondemand radio-resources [7], [17]- [19].…”
Section: B Uav-aided Wireless Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The road to realize 6G networking includes radical departures from conventional wireless architectures, where highly dynamic nodes are deployed to different network areas, ensuring increased resiliency against outages [15], [16]. Moreover, UAVs act as an intermediate layer to terrestrial and satellite segments, providing connectivity in remote and rural environments, fast recovery from disasters, and ondemand radio-resources [7], [17]- [19].…”
Section: B Uav-aided Wireless Networkmentioning
confidence: 99%
“…the one with the lowest power at the reception, is decoded without any interference. The feasible {S→R} link set is denoted by F n SR with cardinality of F n SR , considering that after SIC, the UAV has managed to decode packets from n maritime sources, and that the set's members fulfill (15).…”
Section: A {S→r} Transmissionmentioning
confidence: 99%
“…The authors found that NOMA‐assisted UAV systems outperformed conventional UAV communication systems. A heterogeneous network (HetNet) using full‐duplex (FD) communication under NOMA‐assisted multi‐UAV transmission was investigated by the authors of [10] to assess inadequate spectra in UAV communications. By featuring more UAVs at lower level altitudes due to the demand for stronger signals, the authors demonstrated the effectiveness of NOMA‐assisted multi‐UAV communications under FD HetNets in terms of achieving higher ergodic sum capability and ergodic capacity gains than half‐duplex HetNets.…”
Section: Introductionmentioning
confidence: 99%
“…By basing on NOMA designs, a multiobjective joint optimization of resource and power allocation was well addressed in [15] while ensuring the minimum transmit power. There has been a number of works that focused on utilizing NOMA in UAV communication system [16]- [30], [32]. Ernest et al [16] computed the ergodic capacity of NOMA-aided systems with a great aim of alleviating the spectrum dearth.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a number of works that focused on utilizing NOMA in UAV communication system [16]- [30], [32]. Ernest et al [16] computed the ergodic capacity of NOMA-aided systems with a great aim of alleviating the spectrum dearth. In virtue of moment generating function (MGF) technique, and together with stochastic geometry; it was proven that unlike half duplex (HD), higher spectrum efficiency is attainable in NOMA aided full duplex (FD) -HetNets.…”
Section: Introductionmentioning
confidence: 99%